Islamic Religious Education Courses as Students Forming Islamic Character - Faizal, Faizal (Jurnal Riset Ilmu Pendidikan, 2022)
National education aims to form Indonesian people who believe and are devoted to God Almighty. Based on that goal, a Religious Education course was made to shape the character of the faithful and pious human being. So far, Islamic education has been felt only to form humans to practice the teachings of Islam only in the aspect of worship, but it is still lacking in forming humans who respect diversity, making differences commonplace, so that social values ??that also underlie Islamic teachings are lacking. correctly understood. Based on these conditions, it is necessary to integrate Islamic Religious Education courses with other subjects such as Pancasila, so that the understanding of religion and its social values ??is also practiced and internalized by students